Teacher Strategies In Improving Islamic Education Learning Outcomes At Mdta Al-Athfal - Bahyati, Bahyati; Inayah, Bidayatul; Farhanudin, A; Humaeroh, Tatu; Rafiudin, Rafiudin (Arfannur: Journal of Islamic Education, 2025)
This research aims to identify teacher strategies for improving learning outcomes in Islamic Religious Education (IRE) subjects. Initial observations indicate that some teachers still lack optimal teaching strategies for achieving maximum learning results. Therefore, this study outlines several effective strategies that can be implemented.  The research employed a qualitative method with a Field Research approach, conducted at MDTA Al-Athfal Lijajar, Ciwandan District, Cilegon City, Banten.The significance of this study lies in its contribution to Islamic education literature, specifically by providing practical guidance for educators to enhance the effectiveness of IRE instruction amidst various challenges. The study also highlights the importance of a holistic approach that integrates improved teacher quality, school standards, conducive learning environments, and the cultivation of good character. The novelty of this research lies in its identification and elaboration of four specific strategies proven effective at MDTA Al-Athfal Lijajar, a local context that may not have been extensively documented. These four strategies include: first, enhancing the knowledge quality of human resources (teachers); second, improving overall school standards; third, creating a comfortable and conducive learning environment; and fourth, instilling good character among students. These findings offer new empirical insights into best practices for improving IRE learning outcomes that can be replicated or adapted in similar educational institutions.